Resource use efficiency and profitability of potato production in Syangja district, Nepal - Chaulagai, Bibas; Sapkota, Poonam; Tiwari, Narayan Prasad (Journal of Agriculture and Natural Resources, 2025)
Potato (Solanum tuberosum L.) is an important cash crop and a key contributor to food security in Nepal, but its productivity is limited by inefficient input use and low adoption of improved practices. This study seeks to bridge that research gap by examine the factors of potato production on farms of varying sizes in Syangja district of Nepal. Field survey was conducted from April 2024 to June 2024 in the Galyang, Bhirkot, Waling, and Chapakot municipalities of Syangja district. Primary data was collected from 91 potato farmers, who were then categorized into small scale and large scale farmers according to their area under potato cultivation. The Cobb-Douglas production function and regression analysis were applied. To ensure the validity of the results, t-tests, chi-square tests, and multicollinearity diagnostics using the variance inflation factor (VIF < 5) were conducted. Large-scale farmers demonstrated a 9% lower variable cost (NRs. 18,232 vs. 19,969/Ropani), but comparable profitability (Benefit-cost ratio: 2.09 vs. 1.86). This may be due to the higher bargaining power of small-scale farmers. The presence of overused inputs like seeds, labor, and fertilizer, where (Marginal Value Product/Marginal Factor Cost < 1), lowered efficiency, while transport (β = 0.24), and post-harvest costs (β = 1.09), were revenue drivers. Semi-commercial and commercial systems of agriculture increased production by 237 to 293 kg/ropani (p < 0.05) over traditional agriculture. Among the commonly cultivated varieties, Khumal Ujjwal exhibited the highest production, with average yield of 940.10 kg/ropani. Return to scale was found to be 1.40, indicates thescaled inputs led to higher productivity in potato production. Therefore, it is suggested to provide training and extension supports on proper utilization of inputs, increase scale of production and post-harvest management.